2015
DOI: 10.1016/j.fertnstert.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of monochorionic twins conceived by assisted reproduction

Abstract: Objective: To evaluate monochorionic twins conceived by assisted reproductive technology (ART). Design: We compared perinatal outcomes of monochorionic twins conceived by ART with their dichorionic counterparts and with spontaneous monochorionic twins. Setting: Referral center. Patient(s): Mothers to monochorionic and dichorionic twins conceived by ART and spontaneous monochorionic twins. Intervention(s): None. Main Outcome Measure(s): Maternal characteristics, pregnancy complications, and perinatal outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 8 publications
4
41
0
Order By: Relevance
“…Furthermore, ART monochorionic twins are also at increased risk of adverse perinatal outcomes compared with spontaneous monochorionic twins. In fact, in monochorionicity ART appears to increase the already high risk of PTB <32 weeks (OR 2.9, 95 % CI 1.1 to 7.3) and VLBW (OR 5.9, 95 % CI 2.5 to 1.49) [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ART monochorionic twins are also at increased risk of adverse perinatal outcomes compared with spontaneous monochorionic twins. In fact, in monochorionicity ART appears to increase the already high risk of PTB <32 weeks (OR 2.9, 95 % CI 1.1 to 7.3) and VLBW (OR 5.9, 95 % CI 2.5 to 1.49) [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Rising rates of multifetal gestations are associated with ART and also with increasing maternal age at delivery [19][20][21][22][23] . The multiple birth rate increased to 71 per 1,000 live births for maternal age over 40 at conception compared to 16.3 per 1,000 at age 20.…”
Section: Epidemiologymentioning
confidence: 99%
“…Often, this is due to other inherent morbidities experienced by MCDA twins, such as IUGR and preeclampsia [59] . Simoes et al [60] studied fetal outcomes of twin gestations based on chorionicity only in ART mothers and found that MCDA twins conceived by ART were significantly more likely to be delivered preterm and to have lower birth weights. The higher prematurity rates also led to an increased early neonatal death rate in MCDA twins.…”
Section: Preterm Birthmentioning
confidence: 99%
“…This study was aimed to double-check the findings of Simoes et al [10] who found that MC twins after assisted reproductive techniques (ART) are at increased risk of adverse perinatal outcomes compared with spontaneous MC twins and with DC twins conceived by ART. However, the population-based study performed by Trojner Bregar and her colleagues [11] …”
mentioning
confidence: 99%
“…This study was aimed to double-check the findings of Simoes et al [10] who found that MC twins after assisted reproductive techniques (ART) are at increased risk of adverse perinatal outcomes compared with spontaneous MC twins and with DC twins conceived by ART. However, the population-based study performed by Trojner Bregar and her colleagues [11] disagreed with the hospital-based results of Simoes et al [10] and suggested that MC twins following ART have similar perinatal outcomes compared to spontaneous MC twins as well as to DC twins conceived by ART.…”
mentioning
confidence: 99%